Protection of Environmental Rights for Sustainable Development: An Appraisal of International and National Laws - Ansari, Abdul Haseeb; Abdulkadir, A.B.; Yamusa, Shehu Usman (AENSI Publications, 2012)
Abstract: There is a close nexus between sustainable management, use and utilization of the environment and safeguard of environmental rights. Both are equally important for the wellbeing of the human kind, but this warrants striking a balance between them. It is for this reason that law has to provide for abatement and control of degradation of the environment and protection of environmental rights. At international level, early human rights instruments made no direct mention of protection of environmental rights, but they, in effect, safeguard them. The later ones have direct mention about protecting these rights. The Aarhus Convention is notable among them. It specifies environmental rights as: rights to access to relevant environmental information, right to participate in environmentalrelated decision-making, and right to access to justice. This paper attempts to critically examine the provisions of these conventions. At national level, some states grant environmental rights under right to life enshrined in their constitutions with specific provision for protection of these rights. Some other states have imposed duties, through their constitutions, as not to pollute the environment. The authors are of the opinion that the effect of all is the same. The courts both internationally and nationally have played a proactive role in ensuring environmental rights are provided in various legal instruments. In some countries, judicial activism has demonstrated a mark distinction by relaxing the requirement of locus standi for facilitating public interest litigations, which has, in effect, brought justice to the doorsteps of the poor and least resourceful people, because availability of such rights will have no value unless procedural impediments are not eased. The authors are of the opinion that the requirement of locus standi should be relaxed in all countries in the interest of general public. Key words: Environmental rights, sustainable development, international laws, national laws